IMPACT OF THE EDUCATIONAL PROGRAMMES FOR PARENTS OF INFANTS ON THE QUALITY OF THE INFANT'S LIFE - M.I. Ivardava (Union of pediatricians of Russia, 2010)
The article focuses on the need to enhance the knowledge of infant parents. Through joint efforts, the pediatrician and parents could substantially improve the quality of the infant's life. Increasing morbidity rates among infants' population make the actual search for methods of improving infants' health, particularly through enhancement of parents' skills in care for infants, upbringing and communication with infants. The article illustrates a research in 4 different areas in which parents' education was provided. The quality of life before and after completion of these programmes is demonstrated. Key words: parents' education, children, neuropsychic development, quality of life. (Pediatric Pharmacology. - 2010; 7(2):52-58)